Gender, competition and the effect of feedback and task: An experiment - Alexandra Baier; Brent J. Davis; Tarek Jaber-Lopez; Michael Seidl (Hans-Böckler-Stiftung, 2018)
This paper investigates the role of feedback in inducing men and women to enter competition. Literature suggests that the underrepresentation of women in management roles and the ensuing gender pay gap might be attributed to differences in preferences for competition, confidence, or risk aversion. A laboratory experiment by the authors found that providing feedback on rank and giving participants the option to compete in their preferred task encourages more women to enter competition. Furthermore, feedback affects reported beliefs and improves efficiency. This study thus provides evidence that manipulating the type of feedback given might be an effective way of closing the gender gap.
urn:nbn:de:101:1-2018040415835
Keywords: 330; competition; gender gap; experiment; feedback